2016
DOI: 10.7705/biomedica.v36i3.3014
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin transporter gene (5-HTT) polymorphism and major depressive disorder in patients in Bogotá, Colombia

Abstract: Introduction:The 5-HTT short allele has been controversially associated with an increased risk of major depressive disorder. Objective: To determine the association of 5-HTT short allele with major depression in Bogotá, Colombia. Materials and methods: We carried out a study of cases (n=68) matched 1:1 with controls by gender and age (±5 years). Major depression was diagnosed using the Mini-International Neuropsychiatric Interview, and 5-HTT polymorphism using PCR. Results: Females were predominant (82.4%). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 59 publications
0
2
0
1
Order By: Relevance
“…However, the results of those studies were conflicting. For example, some studies with various samples showed positive association for polymorphisms of SLC6A4 [22,[46][47][48][49][50][51][52][53] while others did not confirm such findings [54][55][56][57][58]. The same tendency was seen for the polymorphisms of SLC6A2 [59][60][61], which may indicate a possibility of false positive results.…”
Section: Genes Involved In Neurotransmition Through Regulation Of Cal...mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the results of those studies were conflicting. For example, some studies with various samples showed positive association for polymorphisms of SLC6A4 [22,[46][47][48][49][50][51][52][53] while others did not confirm such findings [54][55][56][57][58]. The same tendency was seen for the polymorphisms of SLC6A2 [59][60][61], which may indicate a possibility of false positive results.…”
Section: Genes Involved In Neurotransmition Through Regulation Of Cal...mentioning
confidence: 99%
“…Two studies [15,16] delivered results of meta-analyses, in which two SNPs showed significance. Four studies found significant associations only after population stratification by gender: in the women subgroup [17,18], in the men subgroup [19,20]; one study enrolled only female participants [21]; and one study presented significant results in a particular age group of 37 years or older participants [22]. The genotyping methods and main tests for statistical analyses used in the studies are summarized in Table S2 (Table S2: Summary of genotyping and statistical methods used in the eligible studies).…”
Section: Summary Of Eligible Studiesmentioning
confidence: 99%
“…La DP es una enfermedad mental común que se caracteriza con bajo ánimo, pérdida de interés o placer, energía disminuida, sentimientos de culpa o baja autoestima, alteraciones del sueño o apetito, y mala concentración (5) . Un factor relacionado al desarrollo de síntomas depresivos es la variación genética o polimorfismo de la región promotora del gen transportador de la serotonina (5-HTTLPR) (6) . Un polimorfismo es una variación en la secuencia de un lugar determinado del ADN en los cromosomas de los individuos de una población (7) .…”
Section: Introductionunclassified